Mapping the Landscape: A Bibliometric Examination of Recent Advances in Financial Inclusion - Dipak Singh Rawat (Journal of Nepalese Management and Research, 2024)
There has been a significant increase in research on financial inclusion worldwide, driven by its potential to alleviate poverty, foster economic development, and enhance social equity. To delve deeper into this area, this bibliometric study offers a detailed analysis of the research landscape in financial inclusion from 2015 to 2024, using advanced bibliometric tools like Biblioshiny and VOS viewer. The dataset comprises 1,503 articles from 488 sources, demonstrating a robust annual growth rate of 25.91% in scholarly output. Key findings include identifying prolific authors and influential institutions, such as Asongu SA and the World Bank, and mapping collaborative networks among researchers globally. Thematic evolution reveals a shift from foundational topics like economic growth to emerging themes such as digital finance and sustainable development. This study provides essential insights for researchers and policymakers aiming to enhance financial access and equity worldwide.